Relación Entre La Intención De La Elección De La Carrera De IngenierÃa Civil Y La Iniciativa Emprendedora De Los Estudiantes De Una Institución De Educación Superior Tecnológica En Hidalgo, México - Yessica, GarcÃa-Hernández; Isabel, Mendoza-Saldivar; Leiry Desireth, Romo-Medellin (European Scientific Journal, ESJ, 2017)
In the last years, entrepreneurship has generated a strong interest like potential generator of opportunities and professional growth and economics being the Institutions of Higher Education (IES), the link to transmit in the students the competences and skills required that help to boost the enterprising activity. The objective of this paper is to analyze the intention of the selection of a Civil Engineering degree from students of an Institution of Higher Technological Education in Hidalgo, Mexico, based on the Theory of Planned Behavior, with the goal to identify its relationship with the Degree of Entrepreneurship. The GUESSS instrument adaptation was applied, a sample of n=198 students. The type of research in quantitative approach, descriptive and relational scope. The results showed that the intention to choose the career to undertake at the end of their studies is 67.7%, increasing to 81.8% five years after concluding their studies. Regarding the scales that determine the Entrepreneurship Initiative, the one that has a greater perception of the media on the part of the students is Entrepreneurial Intent and the one of low Score is Control of Perceived Behavior. Finally, Pearson’s Chi-square value indicates a result of 0.021 which defines that exist a dependency relationship between the students’ career choice at the end of their studies and the Degree of Entrepreneurship.